The Economic and Fiscal Burdens of Disasters in the Pacific - Ilan Noy; Christopher Edmonds (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Pacific Islands face the highest disaster risk, in per capita terms, globally. Examples of catastrophic events in the region include the 2009 tsunami in Samoa, the 2014 floods in the Solomon Islands, and the 2015 cyclone Pam in Vanuatu. Even without these catastrophic events, countries in the Pacific are affected by frequent natural hazards of smaller magnitude. We first evaluate the three main sources quantifying risk in the region: EMDAT, Desinventar, and PCRAFI. We describe these sources and conclude they all underestimate the risk, especially for atoll nations, and because of four important trends with respect to changes in natural hazards as a consequence of climate change. These are: (1) increasing frequency of extremely hot days; (2) changing frequency and intensity of extreme rainfall events causing flash flooding or droughts; (3) increasing intensities and changing trajectories of cyclones; and (4) sea-level rise and other oceanic ecological changes. Financial protection is the one policy area where the Pacific is the most exposed—given the very large role of the public sector in the region. It is also the area where there is probably the most room for easy-to-implement improvement. We end by analysing the applicability of various financial instruments to facilitate both ex-ante and ex-post disaster risk management in the region.
Keywords: Q54; 330; disaster risk; Pacific Islands; Small Island Developing States; SIDS